BPJS Patient Satisfaction As Reviewed From Outpatient Services at Ambulu Community Health Center - Sri Puji Lestari; Hanif Hadinata Utama; Harmawan Teguh Saputra (MEC-J (Management and Economics Journal), 2026)
This study aims to analyze the level of satisfaction of BPJS outpatients with the quality of service at Ambulu Community Health Center and identify the gap between patient perceptions and expectations for each service attribute. This study is a survey study with a quantitative approach. The respondents were 94 BPJS outpatients selected using the Slovin formula. Data collection was conducted through questionnaires, then analyzed using the SERVQUAL method, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The results showed that all SERVQUAL dimensions had negative gap values, indicating that the service received by patients did not fully meet expectations. The empathy dimension had the largest gap value, followed by direct evidence, responsiveness, assurance, and reliability. The CSI calculation results showed a value of 77.61%, indicating that patients were generally in the satisfied category, although this satisfaction was not evenly distributed across all service attributes. The IPA analysis showed that there were two attributes in Quadrant I, namely waiting room seating facilities and staff gratitude at the end of the service, which reflected aspects of physical comfort and service attitudes that were not optimal. These findings indicate that patient satisfaction is more influenced by certain attributes, so special attention is needed to attributes with a high level of importance but still low performance.